TATA KELOLA KEUANGAN DAN KEKAYAAN DESA BERDASARKAN TINJAUAN LEGALISTIK - ika agustina (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2021)
This article aims to describe the extent of the changes in Permendagri Number 20 of 2018, RegardingGuidelines for Village Financial Management, and is a revision of Permendagri 113 of 2014. Regarding VillageManagement Guidelines. And what is the connection with Law 6 of 2014, Concerning Villages. The source ofthe data obtained is secondary data, by obtaining data from various literature on Village Laws, GovernmentRegulations and Permendagri related to Financial Management and Village Wealth. The results of thedescription that the writing did, that Law 6 of 2014, Concerning Villages is a reference for the making andstipulation of Permendagri 113 of 2014 and revised to Permendagri 20 of 2018 concerning Guidelines forVillage Management. The conclusion is from the author's opinion, that there are no very significant changesrelated to the substance, Permendagri 113 of 2014, outlines the articles of the Village Law, and improvementsare confirmed by Permendagri 20 of 2018, Regarding Guidelines for Village Financial Management, strictlyaccording to the task. the main and functions of the Official who is given responsibility for the Village Financeand Wealth Manager.Keywords: Governance, Finance and Village Wealth AbstrakArtikel ini bertujuan ingin mendeskripsikan seberapa jauh perubahan yang ada didalam PermendagriNomor 20 Tahun 2018, Tentang Pedoman Pengelolaan Keuangan Desa, dan merupakan revisi atasPermendagri 113 Tahun 2014. Tentang Pedoman Pengelolaan Desa. Serta apa kaitanya dengan UndangUndang 6 Tahun 2014, Tentang Desa. Sumber data yang diperoleh merupakan data sekunder, denganmendapatkan data dari berbagai leteratur Undang Undang tentang Desa, Peraturan Pemerintah danPermendagri terkait dengan Pengelolaan Keuangan dan Kekayaan Desa. Hasil deskripsi yang penulisanlakukan, bahwa Undang-Undang 6 Tahun 2014, Tentang Desa merupakan rujukan atas pembuatan danpenetapan Permendagri 113 Tahun2014 dan direvisi menjadi Permendagri 20 Tahun 2018 TentangPedoman Pengelolaan Desa. Simpulannya dari pendapat penulis, bahwa tidak adanya perubahan yangsangat signifikan terkait subtansi, Permendagri 113 Tahun 2014, menjabarkan atas pasal-pasal dariUndang-Undang Desa, dan penyempurnaan ditegaskan oleh Permendagri 20 Tahun 2018, Tentang Pedoman Pengelolaan Keuangan Desa, secara tegas sesuai tugas pokok dan fungsi dari Pejabat yang diberitanggung jawab terhadap Pengelola Keuangan dan Kekayaan Desa.Kata Kunci : Tata Kelola, Keuangan dan Kekayaan Desa